Synthesis methods of 1,2,4-triazole-3-thiones: review - Yu. S. Frolova; A. H. Kaplaushenko; T. V. Ihnatova; T. M. Kaplaushenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
1,2,4-Triazole-containing compounds are unique heterocyclic compounds present in an array of pharmaceuticals and biologically important compounds used in drug-discovery studies against cancer cells, microbes, and various types of diseases in the human body.